2019
DOI: 10.1111/cei.13341
|View full text |Cite
|
Sign up to set email alerts
|

Decreased A20 expression on circulating CD56bright NK cells contributes to a worse disease status in patients with ankylosing spondylitis

Abstract: A20, a pivotal anti-inflammatory protein, preserves immune homeostasis and regulates prolonged inflammation. A previous study has shown that A20 expression levels are down-regulated in peripheral blood mononuclear cells (PBMCs) from patients with ankylosing spondylitis (AS). However, the precise role of A20 in reducing autoimmune disorders needs to be further elucidated. In this study, A20 expression was found to be preferentially reduced on circulating CD56 bright natural killer (NK) cells in patients with AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The functional subsets of NK cells were further investigated in AS and the cytotoxic CD16 + CD56 dim subset of NK cells were increased in comparison with healthy individuals ( 293 ). A20 functions as an inhibitor of inflammatory cytokines in several cell types and A20 expression was decreased in the CD56 bright NK cell subset of AS patients compared to healthy individuals ( 294 ). Patients with AS have a higher expression of T-bet compared to healthy individuals especially in NK and CD8 + T cells.…”
Section: Natural Killer Maturation Phenotypes Distribution and Funcmentioning
confidence: 99%
“…The functional subsets of NK cells were further investigated in AS and the cytotoxic CD16 + CD56 dim subset of NK cells were increased in comparison with healthy individuals ( 293 ). A20 functions as an inhibitor of inflammatory cytokines in several cell types and A20 expression was decreased in the CD56 bright NK cell subset of AS patients compared to healthy individuals ( 294 ). Patients with AS have a higher expression of T-bet compared to healthy individuals especially in NK and CD8 + T cells.…”
Section: Natural Killer Maturation Phenotypes Distribution and Funcmentioning
confidence: 99%
“…Kucuksezer et al summarized a substantial number of studies [ 35 ], reporting that HLA-B27, ERAP-1, KIRS, and other AS-related genes can potentially affect the function of NK cells and that some changes in NK cell function can be used to anticipate the response to therapy in patients with AS. According to a study, TNF- α secretion by autologous monocytes was enhanced by circulating CD56bright NK cells in AS patients, and this could contribute to the persistent invasive immunological process in AS, which led to aberrant inflammation [ 36 ]. Jiao et al studied the gene polymorphisms in NK cell receptors and found that due to genetic factors related to HLA-B27, the variation in KIRS and its corresponding specific HLA-C ligand might hinder the role of NK cells in recognizing and eliminating targets in the immune response, thus promoting the development of AS [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated a tissue-protective role of NKp44 + IL-22-producing cells in the gut tissue of AS patients (122). However, another study showed that circulating CD56 bright NK cells in AS patients promoted TNF-α secretion by autologous monocytes, which contributed to a worsened disease status (128). NK cells were thought to play a regulatory role in sJIA, and the dysfunction of these cells in sJIA was strongly associated with macrophage activation syndrome (MAS) (129).…”
Section: Nk Cellsmentioning
confidence: 96%